Self–care teaching of patients with multimorbidity in primary health care - Steponkutė, Justina; Galdikienė, Nijolė (Slauga. Mokslas ir praktika, 2021)
Population who is getting older and the increase of multimorbidity spread amongst it shows that the numbers of people who suffer from more than two chronic diseases will increase. Due to increasing multimorbidity, healthcare professionals have to observe the condition of each patient very carefully, teach how to manage it and help patients to adjust their behavior in order to avoid complications. Multimorbidity requires knowledge not only of separate diseases but also of their combinations. Community nurses have to set the priorities in nursing of patients with multimorbidity, but also to keep in mind other illnesses that the patient have. Only properly chosen methods of teaching improves Self–Care of patients.The aim of the study – to evaluate Self–Care teaching of patients with multimorbidity in primary health care.Research methods. Quantitative research was conducted using a written survey method to collect data. Research participants were the persons (n = 41) diagnosed with two or more chronic diseases.Results. According to the research data, patients with multimorbidity are taught Self–Care in primary health care, but not all possible opportunities of teaching are exploited. Most patients with multimorbidity named that nurses assessed their knowledge of the health and Self–Care and provided them with new additional information; ensured communication with patients for prophylaxis purposes; taught how patients should properly follow their health indicators and highlighted, why it is important; specified what should be the health indicators of patients; encouraged patients to follow health indicators; gave booklets and leaflets which had relevant information on Self–Care.
Keywords: D. Orem’s Self–Care model; primary health care; multimorbidity; Self-Care; Self–Care teaching